More Than Just a Lack of Uniformity: Exploring the Evolution of Public Relations Master's Programs. (June 2017) - Briones, Rowena L.; Shen, Hongmei; Parrish, Candace; Toth, Elizabeth L.; Russell, Maria
Public relations is well known for its adaptability through continual change, and as a result, public relations master's programs have been re-conceptualized to remain rigorous and competitive. To further assess both the state and changes of these programs, 20 in-depth interviews were conducted with administrators of public relations master's programs. Findings highlighted that although many programs have evolved their curricula to meet industry demands toward a more interdisciplinary identity, there are still programs that still model recommendations from the Commission on Public Relations Education (CPRE). These findings could be used to better ground the discipline by ensuring a stronger cohesiveness within public relations master's education.